Spontaneous Abortion is a Trial of Muslim Women’s Faith in Allah: A Qualitative Descriptive Study - Masik, Kanida; Chatchawet, Warangkana; Chunuan, Sopen (Pacific Rim International Journal of Nursing Research, 2022)
Grief over spontaneous abortion of women is related to religion, beliefs, and socio-cultural contexts. In-depth understanding and reflection on the grief experiences of Muslim women after spontaneous abortion can provide essential information for developing holistic and personal care plans for these women. A qualitative descriptive study was conducted in a general hospital in lower southern Thailand. Twelve participants who experienced spontaneous abortion between two months and one year before participating in the study were recruited by purposive sampling. Data were collected through in-depth semi-structured interviews from December 2021 to March 2022 until data saturation. Content analysis was used to analyze the data. Grief experiences were immersed in three themes: (1) responding to the loss (three subthemes: denying the loss, bereavement for losing an expected child, self-blame for causing spontaneous abortion); (2) coping with grief (three subthemes: using religious doctrine to accept the loss, thinking positively about the loss, overcoming the grief by getting support); and (3) bonding between the mother and the unborn child (two subthemes: unbreakable bonding, dealing with nostalgia). The rich findings of this study can serve as a framework to develop nursing practice guidelines to promote grief coping strategies for Muslim women after spontaneous abortion within a suitable cultural and religious context.